2018
DOI: 10.3390/catal8030101
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective and Facile Preparation of Fe2O3 Nanoparticles Decorated N-Doped Mesoporous Carbon Materials: Transforming Mulberry Leaf into a Highly Active Electrocatalyst for Oxygen Reduction Reactions

Abstract: Herein, a promising method to prepare efficient N-doped porous carbon-supported Fe 2 O 3 nanoparticles (Fe 2 O 3 /N-PCs) ORR electrocatalysts is presented. The porous carbon was derived from a biomass i.e., mulberry leaf through a cost-effective approach. The existence of diverse compounds containing carbon, oxygen, nitrogen and sulfur in mulberry leaf benefit the formation and uniform dispersion of Fe 2 O 3 nanoparticles (NPs) in the porous carbon. In evaluating the effects of the carbon support on the Fe 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
0
1
1
Order By: Relevance
“…However, the incorporation of Cu and Fe resulted in higher current density than the pristine MnO 2 . Compared to previous research of catalysts containing MnO 2 , CuO, and Fe 2 O 3 compounds, it was found that their long‐term electrochemical stability has improved [174–183] …”
Section: Resultscontrasting
confidence: 60%
“…However, the incorporation of Cu and Fe resulted in higher current density than the pristine MnO 2 . Compared to previous research of catalysts containing MnO 2 , CuO, and Fe 2 O 3 compounds, it was found that their long‐term electrochemical stability has improved [174–183] …”
Section: Resultscontrasting
confidence: 60%
“…[18][19][20][21] However, recent investigations have indicated that iron oxides, which have been neglected for a long time, can exhibit enhanced electrochemical performance. [22][23][24][25][26][27] For example, Li et al reported that α-Fe 2 O 3 /N-doped carbon nanotubes (CNTs) have superior ORR activity with a lower onset potential of −0.21 V (vs. Ag/AgCl) and a more efficient four-electron transfer process. 25 Chen et al fabricated a catalyst composed of Fe-N-doped carbon foam nanosheets in which carbon-coated Fe 2 O 3 nanoparticles are embedded.…”
mentioning
confidence: 99%